Long-term strategies in patients with unprovoked venous thromboembolism - Prandoni, P. (Phlebologie, 2017)
Once anticoagulation is stopped, the risk of recurrent venous thromboembolism (VTE) over years approaches 40 % of all patients with a first episode of VTE. The risk is twice as high in patients with unprovoked VTE than in those with minor (either transient or persistent) risk factors of thrombosis. Although the latest international guidelines suggest indefinite anticoagulation for most patients with a first episode of unprovoked VTE, strategies that incorporate the assessment of residual vein thrombosis and D-dimer have the potential to identify a substantial proportion of subjects in whom anticoagulation can be safely discontinued. For those patients in whom anticoagulation cannot be discontinued, new opportunities are offered by the availability of low-dose anti-Xa compounds, which have been found to possess an extremely favorable benefit/risk profile.
Keywords: Venous thromboembolism; deep venous thrombosis; pulmonary embolism; anticoagulation; residual thrombosis; D-dimer; direct oral anticoagulants